2015
DOI: 10.1177/0300060515594194
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early intravenous bolus oxycodone or fentanyl in emergence from general anaesthesia and postoperative analgesia following laparoscopic cholecystectomy: A randomized trial

Abstract: Oxycodone relieves immediate postoperative pain significantly better than fentanyl, and is not associated with an increase in side-effects in patients undergoing laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 30 publications
(50 reference statements)
2
24
0
Order By: Relevance
“…Four studies [7,8,11,13] reported this outcome. Choi 2015 [7] and Koch 2008[11] used the following methods to assess sedation: "S, asleep, easily aroused; 1, awake and alert; 2, occasionally drowsy, easily aroused; 3, frequently drowsy, falls asleep during conversation; 4, somnolent, minimal or no response to stimulation". Meta-analysis showed that no difference between oxycodone and fentanyl for sedation score at 2 (2RCTs, N = 127, RR 2.06, 95% CI 0.56 to 7.60, Figure 4).…”
Section: Sedationmentioning
confidence: 80%
See 2 more Smart Citations
“…Four studies [7,8,11,13] reported this outcome. Choi 2015 [7] and Koch 2008[11] used the following methods to assess sedation: "S, asleep, easily aroused; 1, awake and alert; 2, occasionally drowsy, easily aroused; 3, frequently drowsy, falls asleep during conversation; 4, somnolent, minimal or no response to stimulation". Meta-analysis showed that no difference between oxycodone and fentanyl for sedation score at 2 (2RCTs, N = 127, RR 2.06, 95% CI 0.56 to 7.60, Figure 4).…”
Section: Sedationmentioning
confidence: 80%
“…However, only four of them [8,10,12,13] contributed data for meta-analysis. Result showed that oxycodone can significantly reduce the pain intensity than other opioids (fentanyl, alfentanil or morphine) in 30 minutes (2 RCTs [7] found that the pain intensity in oxycodone is significantly lower than fentanyl group in half hours post operation, but this effect did not last longer than 0.5 hours. Koch 2008[11] stated that the intensity of deep abdominal pain was significantly lower in the oxycodone group at arrival, after 30, 60 and 90 min and at discharge from the PACU.…”
Section: Meta-analysis Pain Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies supported that oxycodone may offer advantages over fentanyl for pain control [9,10]. Recent data demonstrated that a lower dose of oxycodone was sufficient to control acute post-operative pain [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, intravenous oxycodone has been used for perioperative pain management [7]. Comparing to morphine or fentanyl, intravenous oxycodone provides better pain relief, especially for visceral pain [8][9][10]. During induction of general anesthesia, previous studies have shown that the attenuation effect of oxycodone on hemodynamic responses is comparable to fentanyl, and the complication rates are also similar between these two opioids [10,11].…”
mentioning
confidence: 99%